How to measure (or not) compliance to eradication therapy (Pharmacy Practice, 2006)
This study aimed to test a novel method of compliance measurement in Portuguese community pharmacy in Helicobacter pylori patients.A case series design was used where compliance indicators were electronically measured, aside with patients’ reports. Experienced adverse drug reactions, perceived benefit of therapy and quality of life were also measured.Mean compliance proportion was 56% and a positive impact on patients’ perceived health status was found. The method used was welcomed by community pharmacists, albeit having an influence on patients’ normal behaviour.